Concept-skill-value mapping effects on concept understanding, logical-spatial skills, motivation, mathematics performance and retention - Belarga, Alona Matulac (2007)
A mind map is concerned with how the mind of an individual functions. To determine the effects of concept-skill-value (CSV) mapping strategy on students' mathematics performance and its two components (problem solving and proving), concept understanding, logical spatial skills, motivation, and retention, was the main purpose of this study. It was conducted through the implementation of ten prepared lessons on triangle congruence and polygons in two schools in Iloilo City. The CSV mapping significantly enhanced students' motivation to learn geometry more than the concept mapping strategy, however, it did not lead to significantly higher scores when compared with no mapping strategy.
Thesis (Ph.D. Mathematics Education)--University of the Philippines Diliman.
Keywords: Mathematics -- Study and teaching (Secondary) -- Philippines -- Iloilo City; Mathematical ability -- Testing; High school students -- Philippines -- Iloilo City